Efektifitas Penggunaan Aplikasi “Post Natal Care” untuk Meningkatkan Pengetahuan dan Dukungan Kader pada Ibu Nifas - Ratna Diana Fransiska; Krisjentha Iffah Agustasari; Diadjeng Setya Wardani (Jurnal Medicare, 2025)
The postpartum period is a crucial period that is prone to physical and psychological complications. Delay in recognizing danger signs and low support from family and the surrounding environment are risk factors for morbidity and mortality in postpartum women. This study aims to develop and test the effectiveness of the Post Natal Care application in increasing the knowledge and support of cadres for postpartum women. The research method used was one group pre-post test, with 68 respondents from cadres in Pagentan Village, Singosari District, Malang Regency. Data were collected through pretest and posttest questionnaire instruments, and analyzed using the Wilcoxon test. The results showed a significant increase in knowledge (p=0.000) and support (p=0.000) after using the application. The application was considered attractive, easy to use, informative, and useful by the majority of respondents. In conclusion, the Post Natal Care application is effective as a digital education media to improve the quality of assistance to postpartum women.